Aesthetics in plural. Popular fashion in Bogotá - Salazar, Edward (2016)
This paper presents the results and considerations of my research on fashion, aesthetics and garments in Bogotá’s popular sectors during the 2011-2012 period, carried out through qualitative measurement techniques such as image analysis, ethnographic observation and interviews. The purpose is to analyze gaps and encounters between popular and hegemonic styles to explain the necessity of a conversation about types of fashion, and pointing out the existence of different aesthetic views that can’t be described by a singular concept. Popular fashion takes, reinterprets and challenges the material culture produced by hegemonic fashion, simultaneously producing it’s own references that must be considered as fashion because of it satisfies the premises of the concept. It reveals the class preconception that exist on the subject.